2003
DOI: 10.1029/2002gl016513
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration and loss of relativistic electrons during geomagnetic storms

Abstract: [1] We analyze the response of relativistic electrons to the 276 moderate and intense geomagnetic storms spanning the 11 years from 1989 through 2000. We find that geomagnetic storms can either increase or decrease the fluxes of relativistic electrons in the radiation belts. Surprisingly, only about half of all storms increased the fluxes of relativistic electrons, one quarter decreased the fluxes, and one quarter produced little or no change in the fluxes. We also found that the pre-storm and post-storm fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
794
2
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 746 publications
(852 citation statements)
references
References 11 publications
40
794
2
2
Order By: Relevance
“…The latter usually resulting in stronger storms (typically Dst < −100 nT) with a shorter recovery phase as compared to CIRs [Tsurutani et al, 2006]. While the electron response to IP drivers is a balance between energization and loss processes operating within the magnetosphere [Reeves et al, 2003], when there are increased fluxes associated with CIR-driven storms, they tend to occur at higher L shells, i.e., radial distances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter usually resulting in stronger storms (typically Dst < −100 nT) with a shorter recovery phase as compared to CIRs [Tsurutani et al, 2006]. While the electron response to IP drivers is a balance between energization and loss processes operating within the magnetosphere [Reeves et al, 2003], when there are increased fluxes associated with CIR-driven storms, they tend to occur at higher L shells, i.e., radial distances.…”
Section: Discussionmentioning
confidence: 99%
“…The relativistic electron flux variability on relatively short timescales, e.g., days, are due to a combination of energization and loss processes acting within the radiation belts, resulting in increased, reduced, or unchanged population levels [Reeves et al, 2003]. The energization of electrons to relativistic energies in the radiation belts is considered to be due to physical processes falling into two large classes, namely, radial transport [e.g., Schulz and Lanzerotti, 1974;Elkington, 2006] and in situ wave-particle energization [Thorne, 2010;Summers et al, 2007;Reeves et al, 2013] (for a recent review, see Millan and Baker [2012]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a review, see the studies of Friedel et al [2002], Brautigam and Albert [2000], and Green and Kivelson [2004]. Reeves et al [2003] show that the net effect of geomagnetic activity on radiation belt dynamics is a delicate balance of acceleration, transport, and losses that can lead to either increased or decreased fluxes or to almost no changes at all.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the dynamic variations of the outer radiation belt are the result of a complicated balance between loss and acceleration processes [e.g., Reeves et al, 2003;Meredith et al, 2003;Summers et al, 2004]. There are currently three types of loss mechanisms to explain the electron flux dropout in the outer radiation belt: adiabatic loss or "Dst effect" [Kim and Chan, 1997]; precipitation loss to the atmosphere via pitch angle scattering with plasma waves Abel and Thorne, 1998;O'Brien et al, 2003;Voss et al, 1998]; and drift loss to the magnetopause and outward radial diffusion [Brautigam and Albert, 2000;Miyoshi et al, 2003;Shprits et al, 2006;Ohtani et al, 2009;Matsumura et al, 2011;Turner et al, 2012;Tu et al, 2014].…”
Section: Introductionmentioning
confidence: 99%